Revival and development of the economy of the countries in the context of them in the project “One belt, one way” - Zaynalov J.R. (Indonesian Journal of Innovation Studies, 2019)
The article is devoted to the characterization of economic development in the framework of the project “One Belt, One Way”. Also, the most deeply studied, the government intervention in the economy. The emphasis is placed on the fact that a large number of difficulties arise that limit this activity and introduce it into a certain framework.